2021
DOI: 10.1111/jbi.14091
|View full text |Cite
|
Sign up to set email alerts
|

Rio de Janeiro and other palaeodrainages evidenced by the genetic structure of an Atlantic Forest catfish

Abstract: Aim:The disjunct distributions of freshwater organisms along coastal drainages are usually explained by palaeodrainages formed during sea-level retreats that connected currently isolated basins, or by river capture from tectonic adjustments between adjoining watersheds. We evaluate the relative importance of these events on the genetic variation of freshwater fishes inhabiting the Serra do Mar in eastern Brazil, a region with steep mountains and pronounced bays.Location: Coastal river drainages in southeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Freshwater fish in contemporary isolated drainages are often the products of historical river evolutions. Therefore, phylogeographical studies of freshwater fish are significant for understanding the historical reorganization or rearrangements of rivers within and among drainages [ 3 , 4 , 5 , 6 ]. The genetic diversity observed within a species is a key facet of biodiversity that reflects the evolutionary history and adaptability of a species as a whole, or its constituent populations [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater fish in contemporary isolated drainages are often the products of historical river evolutions. Therefore, phylogeographical studies of freshwater fish are significant for understanding the historical reorganization or rearrangements of rivers within and among drainages [ 3 , 4 , 5 , 6 ]. The genetic diversity observed within a species is a key facet of biodiversity that reflects the evolutionary history and adaptability of a species as a whole, or its constituent populations [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only does the current configuration of disconnected basins represent barriers to gene flow and contribute to divergence processes by allopatry, but recent studies have also shown the effects of past geomorphological events on population genetic diversity and differentiation in Neotropical fishes (e.g. Camelier et al., 2018; Lima et al., 2021; Thomaz et al., 2017). Among these events, past connections between today's isolated basins are forged by either headwater captures or coastal paleodrainages, which can facilitate dispersal between drainages and range expansion, and possibly promote speciation.…”
Section: Introductionmentioning
confidence: 99%
“…TA B L E 2 Summary results of K2P intraspecific and interspecific genetic distances of the partial fragment of cytochrome C oxidase subunit I gene of Phalloceros, considering the grouping according to the delimitation test PTP and GMYC 1. (Lima et al, 2017(Lima et al, , 2021Souto-Santos, Jennings, & Buckup, 2023;Thomaz & Knowles, 2018Thomaz et al, 2015), likely differing by unconformity temporality in common dispersal routes and/or ecological specialisation (Thomaz & Knowles, 2020), which may be closely related to strong incompatibilities of sexual characteristics between sympatric taxa in Phalloceros (Souto-Santos, Jennings, & Thomaz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings for the phylogeographic structure of P. harpagos support evolutionary diversification scenarios for species from the Brazilian coastal basins and highlight the important role of palaeodrainages. Discrepancies between patterns of genetic structure and palaeodrainage connectivity may indicate alternative dispersal processes in coastal watersheds (Lima et al, 2017, 2021; Souto‐Santos, Jennings, & Buckup, 2023; Thomaz & Knowles, 2018, 2020; Thomaz et al, 2015), likely differing by unconformity temporality in common dispersal routes and/or ecological specialisation (Thomaz & Knowles, 2020), which may be closely related to strong incompatibilities of sexual characteristics between sympatric taxa in Phalloceros (Souto‐Santos, Jennings, & Buckup, 2023; Thomaz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%